A novel maneuver for diagnosis and treatment of torsional-vertical down beating positioning nystagmus: anterior canal and apogeotropic posterior canal BPPV - Octavio Garaycochea; Nicolás Pérez-Fernández; Raquel Manrique-Huarte (Brazilian Journal of Otorhinolaryngology, 2022)
Introduction: In patients with benign paroxysmal positional vertigo, BPPV; a torsional-vertical down beating positioning nystagmus can be elicited in the supine straight head-hanging position test or in the Dix-Hallpike test to either side. This type of nystagmus can be explained by either an anterior canal BPPV or by an apogeotropic variant of the contralateral posterior canal BPPV Until now all the therapeutic maneuvers that have been proposed address only one possibility, and without first performing a clear differential diagnosis between them. Objective: To propose a new maneuver for torsional-vertical down beating positioning nystagmus with a clear lateralization that takes into account both possible diagnoses (anterior canal-BPPV and posterior canal-BPPV). Methods: A prospective cohort study was conducted on 157 consecutive patients with BPPV. The new maneuver was performed only in those with torsional-vertical down beating positioning nystagmus with clear lateralization. Results: Twenty patients (12.7%) were diagnosed with a torsional-vertical down beating positioning nystagmus. The maneuver was performed in 10 (6.35%) patients, in whom the affected side was clearly determined. Seven (4.45%) patients were diagnosed with an anterior canal-BPPV and successfully treated. Two (1.25%) patients were diagnosed with a posterior canal-BPPV and successfully treated with an Epley maneuver after its conversion into a geotropic posterior BPPV. Conclusion: This new maneuver was found to be effective in resolving all the cases of torsional-vertical down beating positioning nystagmus-BPPV caused by an anterior canal-BPPV, and in shifting in a controlled way the posterior canal-BPPV cases of the contralateral side into a geotropic-posterior-BPPV successfully treated during the followup visit. Moreover, this new maneuver helped in the differential diagnosis between anterior canal-BPPV and a contralateral posterior canal-BPPV.